Strategi Pengurusan Kos & Masa Projek Pembinaan di Tapak Bina Akibat Covid-19 - Jamaluthin, Jawadul Shamir; Mohamed, Sulzakimin; Sarpin, Norliana; Zainal, Rozlin (Research in Management of Technology and Business, 2023)
The transmission of the Covid 19 virus has resulted in the suspension of all sectors from operating temporarily including the construction sector. The permission to operate again conditionally has created several challenges that construction companies have to overcome due to the effects of Covid 19 and brought problems in terms of cost and time of construction projects. This study aims to examine the effects of Covid 19 on cost and time management of construction projects on construction sites. There are 3 objectives that form the basis of this study, namely to identify the impact of Covid 19 on the cost of construction at the construction site, study the impact of Covid 19 on the construction project time at the construction site as well as identify the strategies used in managing the cost and time of the construction project as a result of Covid 19. This study uses a qualitative research approach using a structured interview method involving 3 respondents consisting of G6 and G7 contractors registered with the Malaysian Construction Industry Development Board (CIDB) in Johor. The results of the study were analyzed using the thematic method and found that Covid 19 has caused an increase in the cost of not only the cost of building materials which have become more expensive but also the cost of logistics which includes sanitation and maintaining cleanliness at the construction site. In addition, the Movement Control Order (MCO) and Standard Operating Procedure (SOP) at the construction site such as the reduction of workers at the project site because a construction activity at the construction site takes a long time. The use of Industrialised Building System (IBS) helps construction activities on the construction site to be faster and more effective. Meanwhile, rescheduling construction activities by contractor managers is one of the strategies used to avoid losses to the company.